Features and trends in the development of Sino-Russian cooperation in the field of non-traditional security - Jian, Sun (Journal of the Belarusian State University. International Relations, 2024)
The concept of non-traditional security has gained widespread recognition among states in recent decades. For regional and international powers like China and Russia, the non-traditional security domain assumes even greater significance than traditional security during peacetime. These two countries have a longstanding history of cooperation in non-traditional security areas. Amidst the significant geopolitical shifts characterising the contemporary world, both China and Russia have intensified their collaborative efforts in this domain, focusing primarily on scientific and technological, financial, energy, and agricultural sectors. This article analyses the recent developments in Sino-Russian cooperation across these sectors, highlighting notable achievements and persistent challenges. An examination of the tangible outcomes reveals substantial financial investments, close and complementary bilateral partnerships driven by pragmatism, and a positive overall trajectory of development. While certain challenges remain, these are unlikely to impede the accelerating pace of cooperation. It is anticipated that Sino-Russian collaboration in non-traditional security will continue to deepen and broaden in the future.
Keywords: non-traditional security; Russia; China; science and technology; finance; energy; agriculture